A case study of radiation level and natural radionuclide concentration in various soil types of Bachok district, Kelantan Darul Naim / Mohd Rafi Mohd Solleh - Mohd Solleh, Mohd Rafi (2004)
This research project was conducted on a 25.76-km 2 land area in Bachok District, Kelantan. Forty nine soil samples were taken and brought to the Malaysian Institute for Nuclear Technology Research (MINT) laboratory to be analysed for Ra-228 , Ra-226, and K-40 activity concentrations. Three or more soil samples were taken from each soil series. Radiation dose at each sampling point was also measured. Radionuclide concentration measurements were carried out using shielded germanium semiconductor detector of high resolution connected to gamma spectrometer. Radiation dose measurements were carried out using radiation dose digital ratemeter detector. Coordinates of sampling points from the field were used in mapping both radiation dose contour and radionuclide concentration contour map. These were done by using block kriging method in GS+ and MapInfo Professional 6.0 computer program as the tools. Correlations between radiation doses and radionuclide activity concentrations with soil characteristics were carried out by using SAS computer program. Regression analysis was carried out by using Excel programmes. It was found that K-40, Ra-228 and Ra226 mean activity concentrations were at 357.6, 62.9 and 46.5 Bq kg" respectively. Soils with higher clay and silt contents had a higher activity concentration of Ra-226. Soils with a higher sand contents had a lower activity concentration of Ra-226. Soils with higher clay and silt contents had a higher activity concentration of Ra-228. Soils with a higher sand contents had a lower activity concentration of Ra-228. Potassium-40 activity concentration showed no correlation with the percentage of clay, silt and sand. The K-40 may have come from either marine sand or from the fertilizers.